Challenges in Research Policy
VIII, 113 p. 12 illus.
Keywords: This open access volume addresses major challenges in research policy and provides advice on how to approach them. With chapters designed as accessible policy briefs, the book serves as an essential resource for new actors in research policy. It offers evidence-based recommendations on approaching research governance, funding, and evaluation challenges by covering these topics: Identifying and facilitating high quality research Evaluating transdisciplinary research quality Evaluating societal impact The dilemmas of grant peer review How citations relate to research quality Reforming research assessment The use of metrics in academic recruitment Quality criteria and concentration of research funding Balancing basic and external research funding Designing performance-based research funding systems Strategic steering of research at universities The consequences of paying to publish Each chapter combines research with practical advice and provides an overview of the state-of-the-art in research on the specific topic, as well as references for further reading.